Źródła nadziei dla grzeszników w świetle Apokalipsy św. Jana - Siemieniec, Tomasz (Verbum vitae, 2025)
This article seeks to answer the question of the sources of hope for sinners in the Apocalypse of John. The research problem may be summarized as follows: Does God, in any way, reveal to sinners that, despite their present condition, He continues to hold hope for their conversion? The prevailing view is that sinners in the Apocalypse are depicted primarily as the recipients of plagues intended to lead them to repentance. Yet is this the only way God seeks to bring them back to the right path? Is it possible, within the descriptions of these plagues, to discern elements that reveal a God who not only punishes but also offers an opportunity for conversion? The study begins by identifying key expressions in the Book of Revelation that refer to sinners: "inhabitants of the earth,""the dead," and "the men." It then undertakes a synchronic analysis of relevant passages, seeking indications that divine punishment is not absolute. In Rev 14:6, sinners are the recipients of the "eternal gospel," representing a call to repentance. In Rev 14:13, "the dea" are given the promise that even conversion at the final moment of life will be effective. The third designation for sinners—οἱ ἄνθρωποι—leads to a similar conclusion: the plagues that strike them are not an irreversible judgment, but rather a punishment that is partial in both scope and duration.